What should we eat? the vegetarian debate - Schrank, Jeff; Schrank, Christine; Stage Fright Productions (Lake Zurich, Ill. : Learning Seed, 2003)
This program suggests people need a reason to eat meat just as vegetarians need one to avoid it. Viewers decide where they belong on the continuum that ranges from vegan at one end to meat three times a day at the other. And just what is a vegan? They learn the most common reasons for avoiding meat as well as some good reasons to include it in a diet
Title from title screen
Narrator: Steve Matuszak
Featuring Patrick Gagnon, Jessica Charapata, Jimmy Stewart
DVD Format
Keywords: Vegetarianism; Meat -- Health aspects